Do preferences for pop music converge across countries? Empirical evidence from the Eurovision Song Contest - Oliver Budzinski; Julia Pannicke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2016)
The combination of the digitalization of cultural goods and facilitated cross-border availability through the internet fuels a globalization process that is of-ten said to cause a homogenization of demand across countries, in particular, for entertainment goods as music and movies. In the markets for music, this implies that the same hits and the same artists should be popular across countries and cultures. In order to test this hypothesis, we analyze historical voting data of the Eurovision Song Contest, the worldwide biggest live broadcasted international music competi-tion between all countries of the European Broadcasting Union. It covers the period from 1975-2016 where digitalization and internet availability were invented and evolved into mass phenomena. Consequently, according to the outlined theory of homogenization of preferences, voting should have become more concentrated on the leading artists and less focused on regional differences in taste. For the purpose of detecting concentration trends in the points allocation, we employ different indi-cators for measuring concentration. First, we calculate a concentration ratio, repre-senting the accumulated total number of points of the top three, five and ten-placed countries in each year of the contest. Second, we calculate the Herfindahl-Hirschman-Index (HHI) and, third, the Gini-Coefficient for each year. Furthermore, we test trend-lines for statistical significance. The results show, that our analysis cannot support the thesis of preference homogenization. We find no significant trend towards pref-erence convergence. In contrast, some of the employed indicators and methods point towards significant, albeit weak, deconcentration trends in voting behavior for the contest.
Keywords: Z10; L82; F60; C01; 330; cultural convergence; Eurovision Song Contest; media economics; cultural economics; empirical economics